Simulation of tillage, crop residue mulch and nitrogen interactions on yield and water use efficiency of wheat (Triticum aestivum) using DSSAT model - RANI, ALKA; BANDYOPADHYAY, K K; KRISHNAN, P; SARANGI, A; DATTA, S P (The Indian Journal of Agricultural Sciences, 2020)
Field experiment was conducted during rabi season for two years (2014-15 and 2015-16) on wheat cultivar HD- 2967 in a sandy loam soil (Inceptisol) for simulation of evapotranspiration, crop water use efficiency (WUE) and yield of wheat under different tillage (Conventional tillage (CT) and no tillage (NT)), residue (maize residue @ 5 t ha-1 (R+) and without residue (R0)) and nitrogen (60, 120 and 180 kg N ha-1, representing 50% (N60), 100% (N120) and 150% (N180) of the recommended dose of nitrogen for wheat (Triticum aestivum L.), respectively management practices using DSSAT (v 4.6) model. Experimental data of the years 2014-15 and 2015-16 was used for the calibration and validation of the model, respectively. The results showed no significant difference in grain and biomass yield due to tillage and crop residue mulch but it increased significantly with increase in the N levels. The WUE of wheat was also not influenced by tillage but increased significantly with the increase in N levels. The DSSAT model could satisfactorily simulate grain yield (R2 = 0.759), biomass yield (R2= 0.728) and seasonal ET (R2= 0.904) in wheat but simulation of WUE (R2= 0.414) was not significant under different tillage, residue and nitrogen management with acceptable level of accuracy.